Optimizing Supply Chain Management in the Confectionery Industry with Odoo 16 - Mahendra, I Gede Yogi Krisna; Susila, Anak Agung Hary; Githa, Dwi Putra (Journal of Information System and Informatics, 2024)
Innovation is crucial in today’s business world, and one way to achieve it is by implementing a Supply Chain Management (SCM) system. Wikana Konfeksi, a clothing manufacturer based in Denpasar, still relies on manual methods for essential tasks such as tracking purchases, managing inventory, and recording sales. These manual processes often lead to errors, such as inaccurate records, misplaced documents, and delays in communication between departments. To address these challenges, Wikana Konfeksi decided to implement an SCM system using Odoo 16 ERP. This system streamlines business processes, helping the company achieve greater efficiency. The Accelerated SAP framework was used to guide the SCM implementation. The primary steps that comprise this technique are project preparation, business blueprint, realization, final preparation, and go-live support. The system was tested using the User Acceptance Testing (UAT) method, focusing on five key aspects of the Odoo 16 system design. Six staff members from Wikana Konfeksi participated in the UAT process, providing feedback on whether the system met their needs. The test results were overwhelmingly positive, with a score of 286, indicating that the system implementation was successful and more time efficient in carrying out each of its business processes.